Designing of thin sheet plating ship constructions from aluminum alloys with minimization of local welding deformations - Simutenkov, Ivan V.; Drahan, Stanislav V.; Симутенков, І. В.; Драган, С. В. (My University, 2019)
Abstract. In low-tonnage shipbuilding in the manufacture of hull structures made of aluminum alloys, the main method of joining parts is argon-arc welding. However, the high deformation capacity of structural aluminum alloys causes the occurrence of local welding deformations that impair the performance and appearance of the structure. Elimination of residual deformations by editing is associated with significant material and energy costs and does not always ensure satisfaction of the high requirements imposed on the presentation of the product. Therefore, the design of such structures should provide for the possibility of their manufacture with minimal labor input and deformations not exceeding the allowable values. The developed technique provides for the design of typical hull structures of pleasure motor yachts according to the Rules of classification societies or ISO12215-5 standard taking into account technological measures to minimize local welding deformations of thin sheet plating from welding set. Using the example of designing various types of hull structures made of alloy 5083H111, the sequence of selecting the thickness of the section plating, the parameters of the cell of the set, the type and size of welds, ensuring the strength requirements established by the Rules and reducing the residual welding deformations to the allowable limit, is shown. To implement the welding technology, an original design of a welding torch with in-nozzle transverse oscillations of the electrode wire was proposed to reduce the energy introduced into the weld. The torch can be used for mechanized and automatic pulse-arc welding.
Проектування тонколистових суднових корпусних конструкцій з алюмініевих сплавів з мінімізацією місцевих зварювальних деформацій
Simutenkov, I. V. Designing of thin sheet plating ship constructions from aluminum alloys with minimization of local welding deformations = Проектування тонколистових суднових корпусних конструкцій з алюмініевих сплавів з мінімізацією місцевих зварювальних деформацій / I. V. Simutenkov, S. V. Drahan // Shipbuilding & Marine Infrastructure. – 2019. – № 1 (11). – P. 9–17.
Keywords: design; aluminum alloy; technology; welding deformations; low-frequency oscillations of the electrode; проектування; алюмінієвий сплав; технологія; зварювальні деформації; низькочастотні коливання електрода